Ranah Keterampilan/Psikomotor Dalam Teknik Instrumen Assesmen - Aminul Qodat (DIMAR: Jurnal Pendidikan Islam, 2020)
Each learning activity has goals to be achieved. To measure the achievement of learning outcomes that have been implemented, need to be evaluated or assessment. During this time, there are still many educators who assess the ability of learners in terms of cognitive and affective course, but more than that, psychomotor ability has a position that is not less important as one indicator of the development of learners. The psychomotor domain itself is a domain related to skill or ability to act after a person receives a particular learning experience. Like cognitive, this sphere also consists of several levels or levels. In its development, the psychomotor domain is categorized into two groups, namely abstract and concrete skills. Abstract skill consists of five learning abilities that include observing, asking, trying, reasoning and communicating. While the concrete skills according to Simpson's analysis consists of seven levels that include perception, readiness, imitating, accustomed to movement, adept, being a natural movement, and being an original action. Psychomotor assessment instruments consist of questions or instructions and scoring guidelines to assess the performance of learners in carrying out the command / problem. Adapaun psychomotor assessment techniques can be done using performance tests, projects, products, portfolios, and written tests. While the instrument can be a check list, rating scale, and anecdotal notes.